Prunus mume extract and choline treatment in patients with non-alcoholic fatty liver disease estimated by b-mode ultrasonography and hepatorenal index - Petar Avramovski; Miroslav Lazarevski; Maja Avramovska; Stefan Talev; Julijana Petrovska; Vesna Siklovska; Kosta Sotiroski (Babol University of Medical Sciences, 2024)
Background: The aim of this study was to find the difference between the liver function test (LFT) and hepatorenal index (HRI), before and after the administration of Prunus mume (PM) and choline i.e., to find the predictors of the non-alcoholic fatty liver disease (NAFLD) severity according its HRI, during the three-month follow-up period. Methods: LFT, glucose, and lipid tests were determined in 168 NAFLD patients, at baseline and after three-month drug treatment. HRI was calculated by Image J software analyzing the ultrasound images, and according its value, 3 groups of NAFLD were formed. Results: The HRI at baseline (1.3598±0.1744) and after 3 months therapy (1.3061±0.1923) differs significantly (p<0.0001). Plasma glucose (FPG) (p<0.0001), glycated hemoglobin (HbA1c) (P=0.002), alanine aminotransferase (ALT) (p<0.0001), aspartate aminotransferase (AST) (P=0.0006), gamma-glutamil transferase (γ-GT) (P=0.0053), high density lipoprotein cholesterol (HDL-Ch) (p<0.0001) and triglycerides (P=0.041) differ significantly, too. HRI is positively correlated with: HbA1c (P=0.035), ALT (P=0.002), AST (P=0.003), γ-GT (P=0.043), and triglycerides (P=0.002) and inversely correlated with HDL-Ch (P=0.011). In multiple regression results (standard coefficient and p-value), the independent predictors for HRI in NAFLD patients were: HbA1c (0.1443, 0.0004), ALT (0.001142, 0.0081), triglycerides (0.0431, 0.0235) and γ-GT (0.001376, 0.0329). Conclusion: Three-month administration of PM and choline have beneficial effects on the regulation of glucose and lipid metabolism (HDL-Ch), and on LFT. This plant extract significantly reduces the levels of FPG, HbA1c, ALT, AST, γ-GT, triglycerides and increases HDL-Ch. The triglycerides, ALT, γ-GT and HbA1c are positive independent predictors for the severity of NAFLD